IMPLEMENTASI METODE STAR UNTUK MENINGKATKAN KEMAMPUAN GURU MENGEMBANGKAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - I Wayan Widana; I Wayan Sumandya; Ni Putu Dini Prastanti (Universitas Indraprasta PGRI, 2022)
The Independent Curriculum policy has implications to the changes of curriculum structure. All educational activities are directed to achieve Project of Pancasila Student Profile Strengthening. The obstacle encountered is that the development of Project of Pancasila Student Profile Strengthening module has not been able to be carried out optimally. Likewise, Pancasila Student Profile formative and summative assessment techniques are not in accordance with regulatory provisions. It is caused by the lack of teacher’s understanding in developing Project of Pancasila Student Profile Strengthening module and the availability of supporting regulations is very minimal. Meanwhile, the availability of Project of Pancasila Student Profile Strengthening module is necessary. The purpose of this community service activity is to improve the ability of SMK Pariwisata Triatma Jaya Tabanan teachers to develop Project of Pancasila Student Profile Strengthening modules in accordance with the characteristics of school. The method used in this activity is STAR method (Situation, Challenge, Action, Reflection and impact). After conducting the activity, the results are the increase of teachers' understanding to the concepts and mechanisms for developing Project of Pancasila Student Profile Strengthening module, and being able to compile module in accordance with the provisions of applicable laws.